Role of organosolv pretreatment on enzymatic hydrolysis of mustard biomass for increased saccharification - Singh S.; Sinha R.; Kundu S. (My University, 2025)
This study focusses mainly on assessing the effectiveness of acetone organosolv process as a pretreatment strategy on mustard (Brassica juncea) biomass. We used aqueous acetone as the solvent and sulfuric acid as a catalyst for ease of cellulosic saccharification. The acetone organosolv pretreatment of mustard straw and stalk (MSS) biomass was investigated for the effect of acetone concentration (SC), acid catalyst concentration (AC), and treatment duration (t) using a full factorial design of the experiment and subsequent Pareto analysis of their effects. The 23 full factorials design contained 12 runs, each of which was deployed to pretreat weighed amount of MSS biomass. Each of the different products of these 12 runs was further saccharified using cellulase enzyme produced by Trichoderma reesei. Among the variables, the time has a pronounced effect during pretreatment on glucose yield. Since the increase in time from 30 to 90 min caused an increase of 3.39 g/L in glucose concentration, the increase in acid catalyst concentration from 0.2 to 0.4% caused an increment of 0.7 g/L in glucose content, while the rise in acetone concentration from 50 to 80% caused an increment of 0.44 g/L in glucose concentration. The reducing sugars generated after hydrolysis of MSS biomass can be utilised for the production of bioethanol by Saccharomyces cerevisiae. The FTIR data and SEM studies of untreated and treated MSS biomass were performed to indicate the pretreatment of the MSS biomass. Therefore, after pretreatment MSS biomass can be an alternative substrate for bioethanol production. This study is an attempt to promote the valorization of widely available MSS biomass for bioethanol production by using a statistically optimized process. © 2021, The Author(s), under exclusive licence to Springer-Verlag GmbH, DE part of Springer Nature.